(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article is an attempt to linguistic-stylistic analysis of poetic sound fabric of space Nicolas Vingranovskogo. The groups sound systems, disclosed the features of their functioning.